Method for modifying resin side chain group in quantum dot photoresist
By modifying the functional group of the side chain group of the quantum dot photoresist resin to form coordination bonds with the quantum dot surface, the problems of decreasing luminescence efficiency and ligand shedding during the photolithography process are solved, and better compatibility and display effects are achieved.
Patent Information
- Application Number
- CN202411865830.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-25
AI Technical Summary
Quantum dot photoresist may react during photolithography, resulting in a decrease in luminescence efficiency, and the acidity of the resin will cause the quantum dot ligand to fall off, affecting its uniform distribution and luminescence consistency in the photoresist.
By modifying the side chain groups of the photoresist resin functional groups, it contains functional groups that can coordinate with the quantum dot surface, thereby passivating the defects of the quantum dot surface and reducing the impact of the resin acidity on the quantum dots.
The modified photoresist resin can have good compatibility with quantum dots, improve its dispersion degree and luminous efficiency in the photoresist, reduce the impact of free radicals destroying the surface of the quantum dot, and significantly improve the exposure accuracy and display effect.
Smart Images

Figure CN119882350A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quantum dot photoresists, in particular to a method for modifying side chain groups of resins in quantum dot photoresists. Background Art
[0002] Quantum dot photoresist is a new type of material that combines the excellent properties of quantum dot materials with the processability of traditional photoresists. It is mainly used in the field of color conversion technology for microdisplays. The pixel size of microdisplays is extremely small, usually less than 10 microns or even smaller, so the requirements for color conversion materials are extremely stringent. Traditional color conversion technologies, such as phosphors, are difficult to meet the needs of microdisplays for high-performance display effects due to their limitations in resolution, color purity and luminous efficiency. Quantum dots, with their high color purity, narrow-band luminescence and high photoelectric conversion efficiency, have become an ideal choice in the field of color conversion for microdisplays. Quantum dot photoresist can achieve precise micron-level distribution of RGB colors by combining quantum dots with photolithography. This means that the color of each pixel can be finely controlled on the microdisplay, ensuring the high precision and high stability of the color conversion layer, thereby improving the display effect. In this way, quantum dot photoresist can not only improve the resolution of the display, but also significantly enhance the color expression, allowing display devices to show richer and more vivid pictures.
[0003] Although quantum dot photoresist has shown broad application prospects, it still faces many technical challenges in its actual development and application. First, during the photolithography process, quantum dots may react with the chemical components in the photoresist, resulting in a decrease in the luminescence efficiency of quantum dots. Secondly, the optical properties of the photoresist matrix material need to match the luminescence wavelength of the quantum dots to avoid light absorption and scattering and ensure the best luminescence effect. In addition, achieving uniform distribution of quantum dots in the photolithography process and ensuring the luminescence consistency of quantum dots in different regions are also one of the key difficulties in the preparation process. Future research and development directions may focus on how to optimize the formula of quantum dot photoresist to reduce the impact on luminescence efficiency while improving the accuracy and stability of the process. In addition, with the continuous advancement of photolithography technology, it will also be key to develop new photoresist matrix materials that are highly compatible with quantum dot materials. This will promote the large-scale application of quantum dot photoresists in microdisplays and other high-precision display devices, thereby further enhancing the performance capabilities of ultra-high-definition display technology. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a method for modifying the side chain groups of the resin in the quantum dot photoresist, so as to passivate the surface defects of the quantum dots and reduce the influence of the acidity of the resin on the shedding of the quantum dot ligands.
[0005] To achieve the above purpose, the present invention adopts the following technical scheme: a method for modifying the side chain groups of the resin in the quantum dot photoresist, which functionalizes the side chain groups of the photoresist resin so that the side chain groups contain functions that can coordinate with the quantum dot surface.
[0006] In a preferred embodiment, the quantum dots include CdSe, CdS, ZnS, CdZnSe, CdZnS, CdZnSeS, ZnSeS, ZnSe, CuInS, CuInSe, InP, InZnP or perovskite quantum dots, and the emission wavelength covers the visible light range.
[0007] In a preferred embodiment, the side chain groups include one or more organic groups such as phenyl, C1-C18 alkyl, five-membered alkane ring group, six-membered alkane ring group, etc.; the side chain group functional groups include carboxyl, hydroxyl, thiol, carbonyl or amine functional groups, and also include one or more functional groups such as phosphate, phosphoxy, hypophosphite, nitrile, azide, phenylmaleimide, alkenylmaleimide that can form coordination bonds with the surface of quantum dots.
[0008] In a preferred embodiment, the quantum dot photoresist is composed of quantum dots and improved photoresist, wherein the weight percentage of quantum dots is 10-40%, and the weight percentage of improved photoresist is 60-90%; the improved photoresist is composed of photoresist resin, monomer, photoinitiator, solvent, and additive; photoresist resin, weight percentage is 30-70%; monomer, weight percentage is 10-30%; photoinitiator, weight percentage is 1.2-4%; solvent, weight percentage is 15-60%; additive, weight percentage is 0.5-1.5%.
[0009] In a preferred embodiment, the photoresist resin includes one or a combination of polymeric organic compounds such as acrylic resin, polyvinyl alcohol resin, phenolic resin, polyimide resin, etc.
[0010] In a preferred embodiment, the monomer includes one or more of trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, and tripentaerythritol octaacrylate.
[0011] In a preferred embodiment, the photoinitiator includes one or more of 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2,4-diethylthioxanthone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, and 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole.
[0012] In a preferred embodiment, the additives include one or more of a defoaming agent, a leveling agent, a silane coupling agent, and scattering nanoparticles.
[0013] In a preferred embodiment, the solvent includes one or a combination of two of propylene glycol monomethyl ether, propylene glycol methyl ether acetate, diethylene glycol methyl ethyl ether, propylene glycol diacetate, propylene glycol monoethyl ether, and 3-methoxybutyl acetate.
[0014] In a preferred embodiment, the first step of preparing the photoresist is to add the photoresist resin, monomer, photoinitiator, solvent and additive into a mixing container in accordance with a ratio in order to form a mixture under light-proof conditions; the mixture is magnetically stirred for 4-6 hours to fully mix the components; the second step is to place the uniformly mixed photoresist solution in an ultrasonic device for ultrasonic treatment for 0.5-1.5 hours to ensure that the components are evenly dispersed and bubbles are removed; the third step is to filter the photoresist solution after ultrasonic treatment using a nylon filter of 80-120 microns to remove impurities and ensure the purity of the solution to obtain a uniform photoresist solution ; The fourth step is to ultrasonically mix the uniform photoresist solution with the quantum dots for 0.5-1.5 hours, and then the patterned quantum dot film can be realized through process conditions such as spin coating, photolithography or printing; finally, through the mask template overlay mark alignment method in the photolithography technology, the patterned quantum dot film is precisely aligned with the overlay mark on the micro-LED or micro-OLED, so as to realize the display pixel alignment; it is used as a light-emitting layer or color conversion layer in micro-LED or micro-OLED displays, and by controlling the arrangement of quantum dots, a high-resolution and high-contrast display effect can be achieved, and full-color display can be realized.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) After the photoresist resin is modified, the side chain groups can coordinate with the surface of the quantum dots, which can passivate the surface defects of the quantum dots. At the same time, it can reduce the impact of the ligand shedding on the surface of the quantum dots due to the acidity of the resin. The coordination effect can also increase the solubility of the quantum dots and the degree of dispersion in the photoresist.
[0016] (2) The free radicals released by the photoinitiator during the photolithography process will damage the surface of the quantum dots. However, the functional groups contained in the modified groups can absorb the generated free radicals and form coordination bonds with the surface of the quantum dots to play a passivation role, greatly reducing the destructive effect of the free radicals. The functional group modification contained in the side chain group can enhance the cross-linking of the resin and improve the exposure accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The structural formula of the modified photoresist resin obtained by grafting the photoresist resin with the side chain group N-phenylmaleimide according to the preferred embodiment of the present invention; Figure 2 A schematic diagram of the configuration of quantum dot photoresist and the photolithography process flow of a preferred embodiment of the present invention; Figure 3 (a) is the FTIR spectra of the modified resin and the quantum dot-doped resin according to the preferred embodiment of the present invention; Figure 3 (b) is an XPS spectrum of pure quantum dots and quantum dots doped with modified resin according to a preferred embodiment of the present invention; Figure 4 (a) Red and (b) green PL spectra of pure mixed solvent, unmodified photoresist and phenylmaleimide (NPMI) modified photoresist doped with quantum dots; (c) red and (d) green TRPL spectra; (e) red and (f) green PLQY spectra; Figure 5 (a) Red and (b) green photolithographic rectangular array patterns of unmodified quantum dot photoresist; (c) red and (d) green photolithographic rectangular array patterns of phenylmaleimide (NPMI) modified quantum dot photoresist.
[0018] Figure 6 (a) Red and (b) green PLQY spectra of the unmodified and phenylmaleimide (NPMI) modified color conversion films; (c) red and (d) green TRPL spectra. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0020] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0021] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application; as used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or their combinations.
[0022] A method for modifying the side chain groups of resin in quantum dot photoresist, reference Figure 1-6 , the side chain groups of the photoresist resin are functionally modified to passivate the surface defects of the quantum dots and reduce the effect of the acidity of the resin on the shedding of the quantum dot ligands, so that the photoresist prepared by the modified photoresist resin can have better compatibility with the quantum dots.
[0023] The side chain group contains N-phenylmaleimide.
[0024] The modified photoresist resin is formed by grafting with the side chain group N-phenylmaleimide; The photoresist comprises: acrylic resin, 30-70% by weight; monomer, 10-30% by weight; photoinitiator, 1.2-4% by weight; solvent, 15-60% by weight; additive, 0.5-1.5% by weight.
[0025] The monomers include one or more of trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, tripentaerythritol octaacrylate, and the like.
[0026] The photoinitiator includes one or more of 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2,4-diethylthioxanthone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, and the like.
[0027] The additives include one or more of a defoaming agent, a leveling agent, a silane coupling agent, scattering nanoparticles, and the like.
[0028] The solvent includes one or a combination of two of propylene glycol monomethyl ether, propylene glycol methyl ether acetate, diethylene glycol methyl ethyl ether, propylene glycol diacetate, propylene glycol monoethyl ether, 3-methoxybutyl acetate, etc.
[0029] The specific process steps are as follows: Spin coating photoresist: Spin the quantum dot photoresist solution evenly on the surface of the substrate material to form a thin film. The spin coating speed and time can be adjusted according to the required film thickness to ensure the uniformity of the coating.
[0030] Mask exposure: Place the designed pattern mask accurately on top of the photoresist layer, ensuring alignment. Next, expose the photoresist under a 365 nm UV light source with an exposure dose of 30 mj / cm 2 The ultraviolet light causes the photoresist in the unshielded area of the mask to react chemically, forming a predetermined pattern. Development: After exposure, the sample is immersed in a special developer for 40 seconds. This process removes the unexposed photoresist area, leaving behind the patterned quantum dot pixels.
[0031] Example 1 In this study, the interaction mechanism between N-phenylmaleimide (NPMI) side chain groups and CdSe quantum dots was investigated. Pure modified resin and resin doped with CdSe quantum dots were characterized by Fourier transform infrared spectroscopy (FTIR). Figure 3 (a) The FTIR spectrum shows that the C=C vibration absorption peak (1599cm - ¹) and CN vibration absorption peak (1382 cm - ¹) did not change significantly. However, after the incorporation of CdSe quantum dots, the C=O stretching vibration absorption peak increased from 1733 cm - ¹Move to 1716 cm - ¹. This indicates that the introduction of CdSe quantum dots allows Cd to coordinate with the lone pair of electrons on oxygen, weakening the bond energy of the C=O bond and causing the absorption peak to shift to a lower wave number.
[0032] Figure 3 (b) shows the X-ray photoelectron spectra (XPS) of CdSe quantum dots without and with modified resin. The spectrum results show that after being doped with resin, the binding energy of the 3d3 / 2 and 3d5 / 2 electronic energy levels of Cd shifted to the low energy direction by 0.13 eV, reflecting that Cd² + The density of the surrounding electron cloud increases. This phenomenon shows that Cd² + The electrons from the oxygen lone pair in the C=O bond of N-phenylmaleimide further prove that Cd² +The Cd-OC coordination bond is formed between the C=O bond, thereby reducing the Cd² + The defect charge density.
[0033] Example 2 Figure 4 (a) and (b) show the red and green fluorescence emission spectra of the three groups of samples. After the addition of photoresist, the photoluminescence intensity of the solution decreased. This is because the acidic environment in the photoresist affects the ligands on the surface of the quantum dots, causing some ligands to fall off, thereby increasing the surface defects of the quantum dots. However, the coordination bond formed by the C=O bond in the N-phenylmaleimide (NPMI) group and Cd has a passivating effect, which can reduce the generation of quantum dot defects. Therefore, when the modified resin is added, the photoluminescence intensity is enhanced compared to the unmodified resin.
[0034] Figure 4 (c) and (d) show the red and green time-resolved photoluminescence spectra and their fitting curves of the three groups of samples, respectively. The fitting results are summarized in Table 1. From the data, it can be seen that in the photoresist prepared based on the unmodified resin, the average lifetimes of the red and green quantum dots are 37.38 ns and 11.71 ns, respectively, while in the modified resin, the average lifetimes of the red and green quantum dots increase to 39.82 ns and 14.25 ns, respectively. This result further verifies the effectiveness of N-phenylmaleimide in passivating the surface of quantum dots, reducing the generation of defects and extending the lifetime of quantum dots.
[0035] Figure 4 (e) and (f) show the red and green PLQY test results of the three groups of samples, and the fitting results are also summarized in Table 1. The results show that after the addition of ordinary resin photoresist, the red PLQY dropped to 67.4% and the green PLQY dropped to 34.2%; in the photoresist doped with modified resin, due to the better dispersion of quantum dots and a certain passivation effect, the red and green PLQYs are maintained at 76.1% and 43.4%, respectively.
[0036] Table 1 TRPL and PLQY fitting results of red and green quantum dots doped into pure mixed solvent, unmodified photoresist and NPMI modified photoresist Example 3 Figure 5The unmodified and modified photolithographic patterns were shown under a fluorescence microscope, with rectangular arrays of 10 μm × 10 μm and a spacing of 10 μm. It can be observed that the unmodified photolithographic pattern is not accurate enough, resulting in diffusion of the pattern edge and local agglomeration of quantum dots. After modification, the size of the photolithographic pattern is basically consistent with the design size of the mask, and the quantum dots are more evenly distributed. This indicates that the C=C bond in the side chain of N-phenylmaleimide can enhance the cross-linking of the resin, thereby improving the exposure accuracy of the photolithographic pattern. In addition, the C=O bond in the N-phenylmaleimide group can improve the dispersion of the quantum dots after coordination with the quantum dots, further optimizing the quality of the photolithographic pattern.
[0037] Example 4 Figure 6 (a) and (b) show the PLQY test results of the two films, and the fitting results are summarized in Table 2. Compared with the PLQY in the solution, the PLQY of the film is reduced, indicating that the free radicals released by the photoinitiator will damage the surface of the quantum dots during the photolithography process. However, the carbon-carbon double bonds contained in the modified groups can absorb these free radicals, and the carbon-oxygen double bonds play a passivation role by forming coordination bonds with the surface of the quantum dots, which significantly reduces the damage of the free radicals to the quantum dots, so that the red and green PLQYs are maintained at 66.4% and 36.4%, respectively. In contrast, in the absence of modified groups, the destructive effect of free radicals is significant, causing the PLQY of the green and red films to drop to 50.5% and 23.8%, respectively.
[0038] Figure 6 (c) and (d) show the time-resolved photoluminescence spectra (TRPL) of the red and green color conversion films, and the fitting results are summarized in Table 2. From the data analysis, the modified groups have a significant effect on the average lifetime of quantum dots, showing a similar trend to the quantum yield (PLQY). Specifically, the average lifetime of the modified film is significantly higher than that of the unmodified film, indicating that the modified groups effectively extend the luminescence lifetime of the quantum dots. This lifetime extension further proves the protective effect of the modified groups on quantum dots, especially in passivating the surface defects of quantum dots. The modified groups can reduce the non-radiative recombination caused by surface defects, thereby improving the photoluminescence efficiency of quantum dots, extending the luminescence lifetime, and enhancing the overall optical properties of the material.
[0039] Table 2 TRPL and PLQY fitting results of color conversion films with unmodified and NPMI-modified red and green quantum dots
Claims
1. A method for modifying side chain groups of a resin in a quantum dot photoresist, characterized in that: The side chain groups of the photoresist resin are functionally modified so that the side chain groups contain functions that can coordinate with the surface of the quantum dots.
2. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 1, characterized in that: The quantum dots include CdSe, CdS, ZnS, CdZnSe, CdZnS, CdZnSeS, ZnSeS, ZnSe, CuInS, CuInSe, InP, InZnP or perovskite quantum dots, and the emission wavelength covers the visible light range.
3. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 1, characterized in that: The side chain groups include one or more organic groups such as phenyl, C1-C18 alkyl, five-membered alkane ring group, six-membered alkane ring group, etc.; the side chain group functional groups include carboxyl, hydroxyl, thiol, carbonyl or amine functional groups, and also include one or more functional groups such as phosphate, phosphoxy, hypophosphite, nitrile, azido, phenylmaleimide, alkenylmaleimide that can form coordination bonds with the surface of quantum dots.
4. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 1, characterized in that: The quantum dot photoresist is composed of quantum dots and improved photoresist, wherein the weight percentage of quantum dots is 10-40%, and the weight percentage of improved photoresist is 60-90%; the improved photoresist is composed of photoresist resin, monomer, photoinitiator, solvent, and additive; photoresist resin, weight percentage is 30-70%; monomer, weight percentage is 10-30%; photoinitiator, weight percentage is 1.2-4%; solvent, weight percentage is 15-60%; additive, weight percentage is 0.5-1.5%.
5. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 4, characterized in that: The photoresist resin includes one or a combination of polymerized organic compounds such as acrylic resin, polyvinyl alcohol resin, phenolic resin, polyimide resin, etc.
6. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 4, characterized in that: The monomers include one or more of trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, and tripentaerythritol octaacrylate.
7. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 4, characterized in that: The photoinitiator includes one or more of 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2,4-diethylthioxanthone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, and 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole.
8. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 4, characterized in that: The additives include one or more of a defoamer, a leveling agent, a silane coupling agent, and scattering nanoparticles.
9. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 4, characterized in that: The solvent includes one or a combination of two of propylene glycol monomethyl ether, propylene glycol methyl ether acetate, diethylene glycol methyl ethyl ether, propylene glycol diacetate, propylene glycol monoethyl ether, and 3-methoxybutyl acetate.
10. The method for modifying the side chain groups of a resin in a quantum dot photoresist according to claim 4, characterized in that: The first step of preparing the photoresist is to add the photoresist resin, monomer, photoinitiator, solvent and additive into a mixing container in accordance with the ratio in order to form a mixture under light-proof conditions; the mixture is magnetically stirred for 4-6 hours to fully mix the components; the second step is to place the uniformly mixed photoresist solution in an ultrasonic device for ultrasonic treatment for 0.5-1.5 hours to ensure that the components are evenly dispersed and bubbles are removed; the third step is to filter the photoresist solution after ultrasonic treatment using a nylon filter of 80-120 microns to remove impurities and ensure the purity of the solution to obtain a uniform photoresist solution; the fourth step is to After the uniform photoresist solution is ultrasonically mixed with quantum dots for 0.5-1.5 hours, a patterned quantum dot film can be realized through process conditions such as spin coating, photolithography or printing; finally, through the mask template overlay mark alignment method in the photolithography technology, the patterned quantum dot film is precisely aligned with the overlay mark on the micro-LED or micro-OLED, thereby realizing display pixel alignment; it is used as a light-emitting layer or color conversion layer in micro-LED or micro-OLED displays, and by controlling the arrangement of quantum dots, a high-resolution and high-contrast display effect can be achieved, and full-color display can be realized.
Citation Information
Patent Citations
Quantum dot material, quantum dot color film substrate and preparation method
CN111909683A